ANALISIS EFISIENSI DAN NILAI TAMBAH PRODUK AGROINDUSTRI OLAHAN KERUPUK KULIT SAPI - Suprianto Suprianto; Sarifudin Serip (Distribusi - Journal of Management and Business, 2021)
This research takes the title "Analysis of Efficiency and Added Value of Processed Agroindustry Products of  Cow Crackers (Case Study in Seganteng Mataram City). This research was conducted by taking 6 business units, namely the business of processing cow crackers in Seganteng, Sandubaya Subdistrict, Mataram City, which were determined intentionally. The purpose of this study is to analyze production costs and expenditure levels, cost efficiency and value added or Value Added Ratio (RNT).Overall, of the 6 agro-industry business units for making crackers, while the level of business ratio (R / C Ratio), the average value is above 1 or R / C. The ratio is> 1, which is meant by both the business of processing skin crackers (R / C Ratio = 2.43) means that this business is profitable to be undertaken, with the average income obtained by the leather cracker industry in a single production process of Rp. 7,163,263.The added value of the business of processing leather crackers is IDR 7,663,263 and the added value per kg in the production process is (7,633,263: 141 kg) IDR 58,844.33 which means that every 1 kg of cow leather processed into cow skin crackers can be given an added value of 58,844 , 33. The value added ratio (RNT) of 63% means that the value added is high because the RNT is> 50%. means the agro-industry business Making cowhide crackers has good prospects for development,To further increase the added value of the processing agro-industry business (the business of cowhide crackers) the need to further increase operational costs such as the use of fuel, the use of electricity, the purchase of auxiliary materials. In addition it needs new innovations in creating new products that are more attractive to consumers' purchasing power.